Exterior wall of the Suswani Mata Temple - Temples of India Project Team (Jio Institute, 2024)
Seen here is the exterior wall elevation of the Suswani Mata Temple. Few of the base plinth mouldings are buried, however, the mouldings of the vedibandha (basal mouldings) are visible in the order of khura (hoof), kumbha (pot), kalasha (a pitcher), kapotali (cyma recta), followed by the jangha (wall) portion. The part connecting the garbhagriha (sanctum sanctorum) to the mandapa (pillared hall) is abruptly cut during the modern period restorations. Kumbha moulding with motifs, pancharatha (five ratha or projections on each side) plan with bhadra (central offset), pratiratha (intermediary projection or offset) and karna (corner offset) are visible.